If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6x = -11 Combine like terms: 5x + 6x = 11x 11x = -11 Solving 11x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '11'. x = -1 Simplifying x = -1
| X^3-3x^2-9x+3=0 | | (4x-5)(3-2x)=12-9(2x-5) | | 9+2+4=183652 | | 3(5x+6x)=108 | | 4x-72=-36 | | 4(x-14)=160 | | 4t+20-15= | | y=-4x^2+2x-3 | | 0=x^2+20x+208 | | 0=x^2+20+208 | | 40=2x+5+2x-3 | | tanx=0.5714 | | 3x+5(6.5)=37 | | 7(5y-4)=21y | | er^10=2er^1 | | x+3+2(x-4)=28 | | 14n^2+14n=0 | | 0.25x+3.5=20 | | 2k+6=11 | | 0.25x+3.5=0 | | 3(-y+8)+5y=37 | | 3(3+5m)-12+(-3m)= | | 4b-2+7b=20 | | 19-(x+8)=6x+3 | | -4y/4= | | 2(5)-3y=9 | | 2x-3y=y | | 2x-3y=p | | 30=-16t^2+130t+90 | | 3x+22+2x+88=60 | | 3-5f-7-3f=9 | | 7x+1y+2z=46 |